TOWARDS SMART & RESILIENT URBAN SETTLEMENTS IN ASIA & THE PACIFIC A PRO - POOR PERSPECTIVE - Natalja Wehmer (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2012)
Cities and tows are places with the highest population numbers and densities on the planet. They have been the centres of conglomeration, politic, culture, innovation and connectivity within the globalized world. Globally, cities consume more water, food, vast array of raw materials and consume up to 67% of all energy and contribute 71% of all greenhouse gas emissions. They also exhibit the contrast of poverty and wealth in close physical proximity, with slums located right next to the shining high-rises and gated elite communities. This continuous urbanization mainly swells the numbers of low-income households leading to what some experts have termed by “urbanization of poverty”. However, Cities and towns are also entities whose functioning mostly depends on higher order, interrelated systems. The dynamic nature of urban environments and bad inter-relationships between infrastructure, institutions and ecosystems can lead to cascading failures or “complex disasters”. This characteristic makes the urban areas different from surrounding countryside especially in vulnerabilities. The resilience here is defined as the ability to withstand, recover from and reorganize in response to crises to improve by strengthening “resilience characteristic” such as robustness, redundancy and resourcefulness and “resilience performance” such as risk reduction/preparation, response and recovery of various population groups and urban subsystems.